Pemetaan Distribusi Fasies Batupasir “Ar9”, Formas i Duri, Lapangan “Capcin”, Cekungan Sumatera Tengah Berdasarkan Data Log Dan Data Inti Batuan - Aga Rizky (Jurnal Ilmiah Geologi PANGEA, 2014)
ABSTRACT - Object of study is “Capcin” Field, Central Sumatera Basin, which one of PT. Chevron PasificIndonesia‟s field. “Capcin” Field is located approximately 50 km northwest of Duri Field in CPI Rokan Block.“AR9” sandstone is contained in Duri Formation which including of Sihapas Group at “Capcin” Field. Coredata analysis resulted eigth lithofacies which associated with tidal channel, tidal bar, tidal sand flat, andtransgressive lag. Associated facies interpretation data is calibration with well log before doing faciescorrelation. Based on lithofacies and associated facies interpretation getting depositional environment “AR9”sandstone is tide dominated estuary. Keyword : tidal channel, tidal bar, tidal sand flat, dan transgressive lag, tide dominated estuary.